Kinetic alterations of collagen and elastic fibres and their association with cardiac function in acute myocardial infarction - Yu, Yuexin (Mol Med Rep, 2018)
The present study aimed to investigate kinetic alterations of collagen and elastic fibres and their association with cardiac function in the acute myocardial infarction (AMI) heart. AMI was generated in Sprague-Dawley rats by ligation of the left anterior descending coronary artery. Cardiac function was determined using B-ultrasonography, AMI was verified using histopathology. The kinetics of collagen type I/III and elastic fibre were evaluated using immunohistochemistry and western blotting at 1 week (1 w), 2 weeks (2 w), 3 weeks (3 w) and 4 weeks (4 w) post-AMI. Cardiac function was decreased by 78, 70, 50 and 38% at weeks 1, 2, 3 or 4 post-AMI, respectively, compared with the normal heart. Elastic fibre was decreased gradually, demonstrating alterations of 2, 77, 86 or 97% reduction, respectively, at weeks 1, 2, 3 or 4 in the AMI heart. Collagen I fibre was increased 1.4-, 1.5-, 2.9- or 3.9-fold at weeks 1, 2, 3 or 4 respectively, compared with the normal heart. Similarly, collagen III was increased 1.2-, 1.7-, 2.8- or 3.9-fold, following AMI. Kinetics of increased collagen I/III, in combination with decreased elastic fibre in infarcted area following AMI, provided evidence that compromised cardiac function following AMI was due to graduate wound healing/scar formation in the infarcted zone, increased stiffness and reduced flexibility of the heart.